Analisis Lingkungan Eksternal dan Internal Sebagai Dasar Penentuan Strategi Bersaing Pada AZWA Parfume - Khanzul - Akhiar (Universitas Madura, 2020)
Capturing business prospects in the perfume industry amid the current competition, a strategy is needed so that business growth through increasing market share can be achieved, and able to improve long-term corporate performance through identification of both internal and external factors so that the business strategy at AZWA Parfume can be achieved. provide an alternative business development strategy, the stages used are: the input stage using the IFE and EFE matrix, the matching stage using the TWOS matrix and the IE matrix and the decision stage using QSPM.The results showed that the competing strategies carried out were quite good even though they were not maximally seen as being weak in conducting promotions and needed training and development for HR, the weak promotion was due to untrained HR in using information systems, so that sales realization was far from the set targets. Where the actual opportunities that are owned are very large seen from the size of the existing market share. While the threat from competitors is very large with the quality of the production they have. But AZWA Parfume also has an advantage that can win the competition by looking at the many variants of parfume that have a unique, luxurious and halal aroma that can meet consumer needs. From the analysis conducted, it is expected that the company can win the competition by increasing promotion and developing HR